Differences in wage rates for males and females in the health sector: a consideration of unpaid overtime to decompose the gender wage gap - Vecchio Nerina; Scuffham Paul A; Hilton Michael F; Whiteford Harvey A (BMC, 2013)
Abstract Background In Australia a persistent and sizable gender wage gap exists. In recent years this gap has been steadily widening. The negative impact of gender wage differentials is the disincentive to work more hours. This implies a substantial cost on the Australian health sector. This study aimed to identify the magnitude of gender wage differentials within the health sector. The investigation accounts for unpaid overtime. Given the limited availability of information, little empirical evidence exists that accounts for unpaid overtime. Methods Information was collected from a sample of 10,066 Australian full-time employees within the health sector. Initially, ordinary least-squares regression was used to identify the gender wage gap when unpaid overtime was included and then excluded from the model. The sample was also stratified by gender and then by occupation to allow for comparisons. Later the Blinder-Oaxaca decomposition method was employed to identify and quantify the contribution of individual endowments to wage differentials between males and females. Results The analyses of data revealed a gender wage gap that varied across occupations. The inclusion of unpaid overtime in the analysis led to a slight reduction in the wage differential. The results showed an adjusted wage gap of 16.7%. Conclusions Unpaid overtime made a significant but small contribution to wage differentials. Being female remained the major contributing factor to the wage gap. Given that wage differentials provide a disincentive to work more hours, serious attempts to deal with the skilled labour shortage in the health sector need to address the gender wage gap.